2012
DOI: 10.1007/s10856-012-4721-4
|View full text |Cite
|
Sign up to set email alerts
|

Small-diameter tissue engineered vascular graft made of electrospun PCL/lecithin blend

Abstract: In this study, natural lecithin was incorporated into cholesterol-poly(ε-caprolactone) (Chol-PCL) by solution blending in order to modify the performance of the hydrophobic and bio-inert PCL. The fibrous Chol-PCL/lecithin membranes were fabricated by electrospinning, and the surface morphology and properties were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, static water contact angle, and mechanical tensile testing. The blood compatibility of the scaffolds was evaluated by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…While PCL-lecithin is relatively less well-studied in cell growth and tissue engineering, it exhibits high potential for tissue grafts. 15,24 In this study, PCL-lecithin supported the recovery and proliferation of genetically modified cells in a robust fashion ( Figure 5B). In contrast, PCL-gelatin displayed no enhancement over plastic surfaces for recovery and proliferation.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…While PCL-lecithin is relatively less well-studied in cell growth and tissue engineering, it exhibits high potential for tissue grafts. 15,24 In this study, PCL-lecithin supported the recovery and proliferation of genetically modified cells in a robust fashion ( Figure 5B). In contrast, PCL-gelatin displayed no enhancement over plastic surfaces for recovery and proliferation.…”
supporting
confidence: 52%
“…20 Due to its amphiphilic chemical features, which are similar to the phospholipid components of the cell membrane, lecithin can serve as a superior biocompatible support material for cell attachment and growth. Lecithin has been successfully electrospun to fabricate fiber membranes [21][22][23] and the fiber made from a PCL-lecithin blend has been used to construct ureteral 15 and vascular 24 grafts in murine animal models. In addition, a three-dimensional material with a porous structure fabricated from a lecithin-poly (L-lactic acid) blend was used in a rat bone-graft study, 25 demonstrating improved hydrophilicity and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al developed electrospun SDVGs based on lecithin-cholesterol-polycaprolactone and tested them using citrated rabbit blood; hemocompatibility was lower than 1% for these formulations. 21 Woven silk fibroin-based SDVGs produced by Liu et al, 22 phthalized chitosan-based grafts developed by Qiu et al, 13 and poly(diol citrate) grafts developed by Motlagh et al 23 also showed hemolysis of less than 1%. Generally, fluid flow inside small blood vessels is laminar, with very low linear velocity, 24,25 so we set our flow experiments at low Reynolds numbers (Re < 4).…”
Section: Discussionmentioning
confidence: 99%
“…The fibrous membranes and tubular grafts were fabricated by electrospinning using a setup previously described [29]. Briefly, high molecular weight PCL was mixed with PCL-N 3 at blending ratio of 8/2 (w/w).…”
Section: Preparation Of Vascular Grafts By Electrospinningmentioning
confidence: 99%